2020
DOI: 10.1002/agj2.20022
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions and carbon footprint under gravel mulching on China's Loess Plateau

Abstract: Gravel mulching technology has been widely verified as an effective solution to reduce evaporation and improve crop production on China's Loess Plateau, but its impacts on greenhouse gas (GHG) emissions have not been well documented. This study examined the quantification of the overall GHG emissions via estimating global warming potential (GWP), GHG intensity (GHGI), C footprint (CF), and C intensity (CI) with varying experimental treatments. A 2-yr consecutive wheat-maize rotation field experiment was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The results showed that the soil temperature in the whole root zone was affected by soil moisture, and the soil temperature temperature with different degrees, and the suitable range of soil temperature was also different. Ma et al (2015) estab-In conclusion, irrigation amount is a very important factor affecting soil moisture and temperature, which would indirectly affect crop growth, root distribution and yield (Zhang et al, 2016;Liu et al, 2019;Wang et al, 2020). However, most of the existing studies consider the pair relationships among soil, root and crop yield based on unilateral factors (Chen and Liu, 2013), there is a lack of comprehensive studies on the potential effects of different drip irrigation treatments on soil environment, crop root and yield formation (Fan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the soil temperature in the whole root zone was affected by soil moisture, and the soil temperature temperature with different degrees, and the suitable range of soil temperature was also different. Ma et al (2015) estab-In conclusion, irrigation amount is a very important factor affecting soil moisture and temperature, which would indirectly affect crop growth, root distribution and yield (Zhang et al, 2016;Liu et al, 2019;Wang et al, 2020). However, most of the existing studies consider the pair relationships among soil, root and crop yield based on unilateral factors (Chen and Liu, 2013), there is a lack of comprehensive studies on the potential effects of different drip irrigation treatments on soil environment, crop root and yield formation (Fan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During recent years an increasing stream of research has been published on climate effects in relation to different sectors, not the least agriculture. One example is studies on greenhouse gas emissions and C footprint in relation to specific agricultural methods on specific types of soils in specific climate zones (e.g., Wang et al., 2020). Another example is studies on greenhouse effects derived from manure composting (e.g., Bai et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One example Abbreviation: IPCC, Intergovernmental Panel on Climate Change © 2020 The Author. Agronomy Journal © 2020 American Society of Agronomy is studies on greenhouse gas emissions and C footprint in relation to specific agricultural methods on specific types of soils in specific climate zones (e.g., Wang et al, 2020). Another example is studies on greenhouse effects derived from manure composting (e.g., Bai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Greenhouse cultivation is increasing in scale in line with other developments in modern agriculture that have made agriculture a major driver of economic development (Gong et al, 2020;Liu et al, 2018;Wang et al, 2020). Control of the greenhouse environment through management of the microclimate and controlled irrigation promotes healthy crop growth, increased crop yield, and increased fruit quality (Liu et al, 2019b;Shamshiri et al, 2018;Wang and Zhou, 2017).…”
mentioning
confidence: 99%